1998
DOI: 10.1002/(sici)1096-8628(19980413)76:5<402::aid-ajmg7>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

CHARGE syndrome: Report of 47 cases and review

Abstract: The acronym CHARGE refers to a syndrome of unknown cause. Here we report on 47 CHARGE patients evaluated for the frequency of major anomalies, namely coloboma (79%), heart malformation (85%), choanal atresia (57%), growth and/or mental retardation (100%), genital anomalies (34%), ear anomalies (91%), and/or deafness (62%). In addition, we comment on anomalies observed very frequently in neonates and infants with the CHARGE syndrome, including, minor facial anomalies, neonatal brain stem dysfunction with crania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
181
9
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(216 citation statements)
references
References 49 publications
17
181
9
2
Order By: Relevance
“…Consequently, previously reported KS cases associated with congenital heart disease 44 or choanal atresia 45 could in fact represent unrecognised mild CHARGE cases. 46 CHARGE syndrome shares additional traits with the KAL2 genetic form of KS (see below), including cleft lip or palate, present in 20 -35% of KAL2 7,11 -13 and CHARGE 47 patients, external ear malformation, noted in virtually all CHARGE patients 47 and a few KAL2 patients, 48 agenesis of the corpus callosum, reported in several CHARGE 47 and KAL2 patients, 7,13 and coloboma that is highly prevalent in CHARGE patients 47 and has been reported in at least one KAL2 patient too. 7 Most individuals with CHARGE syndrome are heterozygous for loss-of-function mutations in CHD7 that encodes a chromodomain (chromatin organisation modifier domain) helicase DNA-binding protein.…”
Section: Differential Diagnosis: Normosmic Idiopathic Hh and Charge Smentioning
confidence: 99%
“…Consequently, previously reported KS cases associated with congenital heart disease 44 or choanal atresia 45 could in fact represent unrecognised mild CHARGE cases. 46 CHARGE syndrome shares additional traits with the KAL2 genetic form of KS (see below), including cleft lip or palate, present in 20 -35% of KAL2 7,11 -13 and CHARGE 47 patients, external ear malformation, noted in virtually all CHARGE patients 47 and a few KAL2 patients, 48 agenesis of the corpus callosum, reported in several CHARGE 47 and KAL2 patients, 7,13 and coloboma that is highly prevalent in CHARGE patients 47 and has been reported in at least one KAL2 patient too. 7 Most individuals with CHARGE syndrome are heterozygous for loss-of-function mutations in CHD7 that encodes a chromodomain (chromatin organisation modifier domain) helicase DNA-binding protein.…”
Section: Differential Diagnosis: Normosmic Idiopathic Hh and Charge Smentioning
confidence: 99%
“…Gross motor delay in children with CHARGE can be attributed in large part to vestibular dysfunction since the Mondini defect and the associated vestibular anomalies are a frequent finding [Tellier et al, 1998;Wiener-Vacher et al, 1999;Satar et al, 2003]. However, the delay can also be affected by lack of upper visual fields secondary to ocular…”
Section: Emerging Featuresmentioning
confidence: 99%
“…Neuroanatomical anomalies have been reported in CHARGE syndrome (Becker, Stiemer, Neumann, & Entezami, 2001; Bergman, Bocca, Hoefsloot, Meiners, & van Ravenswaaij‐Arts, 2011; Issekutz, Prasad, Smith, & Blake, 2005; Lin et al, 1990; Sanlaville et al, 2006; Sanlaville & Verloes, 2007; Tellier et al, 1998). Lin et al (1990) identified CNS anomalies in 55% ( n  = 26/47) and Tellier et al (1998) in 79% ( n  = 37/47) of CHARGE syndrome patients.…”
Section: Introductionmentioning
confidence: 99%